X-Ray Dips and Polarization Angle Swings in GX 13+1 - Di Marco, Alessandro; La Monaca, Fabio; Bobrikova, Anna; Stella, Luigi; Papitto, Alessandro; Poutanen, Juri; Baglio, Maria Cristina; Bachetti, Matteo; Loktev, Vladislav; Pilia, Maura; Rogantini, Daniele (American Astronomical Society, 2025)
We present the result from the 2024 April observation of the low-mass X-ray binary GX 13+1 with the Imaging X-ray Polarimetry Explorer (IXPE), together with Neutron Star Interior Composition Explorer and Swift- X-Ray Telescope coordinated observations. Two light-curve dips were observed; during them, the harder Comptonized spectral component was dominant and the polarization degree (PD) higher than in the softer, off-dip intervals. Through a joint analysis of the three IXPE observations, which also included the dip from the first observation, we demonstrate that the polarization properties varied in response to the intensity and spectral hardness changes associated with the dips. The PD attained values up to similar to 4%. The polarization angle (PA) showed a swing of similar to 70 degrees across the dip and off-dip states, comparable to the continuous rotation seen during the first IXPE observation. We discuss these results in the context of models for polarized emission from the accretion disk and the boundary/spreading layer on the neutron star surface. We also draw attention to the role that an extended accretion disk corona or disk wind can play in generating high PDs and, possibly, swings of the PA.